18FDG PET-CT in sporadic Creutzfeldt-Jakob disease, correlated with MRI and histology - Morley, Nicholas; Hofer, Monika; Wilkinson, Philip; Bradley, Kevin (World Journal of Nuclear Medicine, 2021)
We present a case of sporadic Creutzfeldt–Jakob disease with profoundly abnormal 18fluoro-deoxy-glucose positron emission tomography with computed tomography (FDG PET-CT) at an early stage, and correlate this with the clear findings at magnetic resonance imaging and also postmortem histology. Prion diseases are rare but important causes of cognitive impairment. The role of FDG PET-CT is discussed, along with other investigations such as electroencephalography and cerebro-spinal fluid analyses.
Keywords: Dementia; magnetic resonance imaging; positron emission tomography; prion diseases